A Strategic Partnership Between Michigan State University and Babeș-Bolyai University: Building an International Educational Hub - Călin Emilian HINŢEA (Transylvanian Review of Administrative Sciences, 2012)
The cooperation between Michigan State University and Babeș Bolyai University has started more than 17 years ago with traditional faculty members’ exchanges and since then has further grown into a strategic partnership. This partnership is now moving toward an important step namely the establishment of an educational hub in Cluj- Napoca, Romania.